Corporate killing for Malaysia a preliminary consideration - Hasani Mohd Ali, (Fakulti Undang - Undang, 2009)
Corporate killing is recognised in UK and Australia. Corporate killing is an extension of the concept of corporate criminal liability. The applicability of the concept in Malaysia is however undeveloped. This is unfavourable as corporate criminal liability may serve as a monitoring mechanism for the corporate regulatory framework, in that, the corporations will need to take into account risks of prosecutions in their managements. Likewise, the public would also benefit through its deterrent effect. This paper highlights that even though the corporate criminal liability suffers from some conceptual problems, it deserves more appraisal in Malaysia and corporate killing is a logical consequential recognition